An Sb-doped p-type ZnO nanowire based random laser diode. (14th January 2016) - Bashar, Sunayna B; Suja, Mohammad; Morshed, Muhammad; Gao, Fan; Liu, Jianlin
Abstract: An electrically pumped Sb-doped ZnO nanowire/Ga-doped ZnO p–n homojunction random laser is demonstrated. Catalyst-free Sb-doped ZnO nanowires were grown on a Ga-doped ZnO thin film on a Si substrate by chemical vapor deposition. The morphology of the as-grown titled nanowires was observed by scanning electron microscopy. X-ray photoelectron spectroscopy results indicated the incorporation of Sb dopants. Shallow acceptor states of Sb-doped nanowires were confirmed by photoluminescence measurements. Current–voltage measurements of ZnO nanowire structures assembled from p- and n-type materials showed a typical p–n diode characteristic with a threshold voltage of about 7.5 V. Very good photoresponse was observed in the UV region operated at 0 V and different reverse biases. Random lasing behavior with a low-threshold current of around 10 mA was demonstrated at room temperature. The output power was 170 nW at 30 mA.